Reliability based structural design of river–sea tankers: Still water loading effects - Motok, Milorad; Momčilović, Nikola; Rudaković, Stefan (Marine structures, 2022)
More than twenty years ago it was acknowledged that methods used in ship design, which affect safety of the vessel, are less sophisticated and modern compared to those used in some other industries, for instance aeronautics or nuclear. The most apparent response to this setback was enforced development of reliability based methods for ship structural design. Implementation of those in the state-of-the-art rules and codes for design of ocean-going vessels is recognizable. However, much less, if anything, was done in this matter for river-sea ships, although a significant portion of their demands and capacity is stochastic in its nature. This paper is aimed to be a pilot research in this field. It uses probability approach to estimate the reliability index of Rule based formulas for still water bending moment, i.e., the probability that thus obtained values will not be overcome by actual, lege artis calculated values. It is based on analyses of more than 400 load cases of 37 prominent river-sea tankers. Acquired results are also input parameters for further analyses, which would include wave induced loads and are the subject of succeeding investigations. •Probability analysis is introduced to river – sea tankers with respect to still water bending moments.•Reliability index is estimated for non-exceedance of still water bending moment, based on statistical data for 37 prominent river-sea tankers.•Comparison is performed to the literature data based on sea – going ships.